Women’s Reproductive Rights in the Stunting Prevention Policy by the Government of Indonesia - Rafida Ramelan; Siti Rochmiyatun; Armasito Armasito (Hakamain: Journal of Sharia and Law Studies, 2025)
This study aims to analyze the protection of women’s reproductive rights in preventing stunting as part of the state’s responsibility to ensure the quality of future generations. The research employed a combination of library research and field research using a qualitative descriptive approach. Data were collected through the examination of legal documents, scholarly literature, government policies, and interviews with health officers, community leaders, and women of reproductive age in regions with a high prevalence of stunting. The findings show that women’s reproductive rights have been protected under various national regulations, including Government Regulation No. 72 of 2021, which demonstrates the government’s commitment to addressing stunting through reproductive health–oriented regulatory policies. However, the implementation of these policies remains suboptimal due to limited coordination among institutions, inadequate public awareness, and disparities between legal norms and field practices. The study concludes that legal protection of women’s reproductive rights is a crucial factor in preventing stunting and ensuring the realization of maqashid al-sharia, particularly hifzhu al-nasl (the protection of lineage). Academically, this research contributes to enriching the interdisciplinary discourse between Islamic law, public policy, and public health by integrating reproductive rights into national stunting prevention strategies. The results are expected to serve as a reference for policymakers and stakeholders in formulating effective, sustainable, and gender-responsive health policies that support the creation of a strong, healthy, and high-quality rabbani generation for the nation’s future.